Learning from Zu˜ni war gods: Repatriating alternative dispute resolution for practice and research - Crampton, Alexandra (Mediation Theory and Practice, 2017)
This article applies lessons learned from the Zu˜ni people of the southwestern United States about successful and sustainable intervention as a metaphor to address common tensions among alternative dispute resolution (ADR) scholars and practitioners. These tensions are found in professionalisation, institutionalisation and identification of best practices. Through example of Zu˜ni efforts to repatriate sacred artefacts known as Ahuy: da, I argue that ADR is an intervention that works best through direct and ongoing dialogue rather than rigid adherence to a set of standards. The problem lies in how such adherence can limit and distort rather than inform or support best practices in research as well as mediation practice. I propose qualitative, ethnographic field research as a way to address this problem, and provide an example from ongoing study of a US family court mediation programme.